PREPARATION AND CHARACTERIZATION OF SELF NANO EMULSIFYING DRUG DELIVERY SYSTEM CONTAINING ANTI-HYPERTENSIVE DRUG’’ - Anukumar E; Nagaraja T S; Yogananda R; Bharathi D R (Journal of Biomedical and Pharmaceutical Research, 2020)
The present work is to prepare and characterization of self nano emulsifying drug delivery system containing Anti-hypertensive drug. Losartan is a competitive antagonist and inverse agonist of angiotensin 2 receptor. The SNEDDS is prepared by Sonication method using a components of SPAN 60/Eudragit RS 100 as a surfactant, PVA as a Co-surfactant, Iso propyl alcohol as a solvent and DCM as a co-solvent. The prepared SNEDDS was evaluated for Fourier transform infrared spectroscopy, Surface morphology, particle size, zeta potential, drug entrapment efficiency, visual assessment, self-emulsification time, Robustness to dilution, in-vitro drug release and short term stability studies. The in-vitro drug release data of all the formulations were found to be zero order over a period of 24 h and Formulation F7 shows good results for the drug release kinetics as controlled release. The stability studies data was found that there was no such difference in drug EE and in-vitro drug release.